Isolation and Identification of Rhizosphere Bacteria Associated with Taro (Colocasia esculenta L. Schott) as Plant Growth Promoting Rhizobacteria - Makitalentu, Feybe; Mustafa, Irfan; Suharjono, Suharjono (Graduate School, Universitas Brawijaya, 2022)
Taro is one of the food crops that has the potential to maintain food security. It has a high carbohydrate content and nutrients with a low glycemic index value. Taro is widely cultivated with intercropping techniques, especially in Kedungkandang District, Malang City. However, this technique caused a decrease in talas tubers production with only 7-10 tons ha-1. This number was lower than the total optimal production with 20.7 tons ha-1 of taro tubers. Plant Growth Promoting Rhizobacteria (PGPR), one of the most potential biofertilizers, can solve this problem with abilities such as phosphate-solubilizing, production of IAA, and nitrogen fixation. This research aimed to analyze the potency and identify the species of taro rhizosphere bacteria that had the best ability as PGPR agents. Taro rhizosphere bacteria were isolated using Pikovskaya medium and TSA (Tryptic Soy Agar) respectively. The PGPR abilities were evaluated on the phosphate-solubilizing, production of IAA, and nitrogen fixation. A total of 12 isolates for phosphate-solubilizing bacteria and ten isolates of IAA-producing bacteria. The highest concentration of phosphate solubilization was P1 isolate, with the concentration of 6.8 μg.mL-1; while I4 isolate had the highest potency for IAA production with the concentration of 23.11 μg.mL-1. Isolates P1 and I4 were selected for the nitrogen fixation ability test. P1 isolate shows the highest ammonia concentration of 2.52 μg.mL-1, and it was identified as Stenotrophomonas rhizophila with a similarity of 99.91% with Stenotrophomonas rhizophila R2A2 67. The potential isolates can be used as PGPR agents or biofertilizers to increase the production of taro plants. Keywords: Colocasia esculenta, IAA, Nitrogen, PGPR, Phosphate.